Performance Comparison of Star Connected Cascaded STATCOM Using Different PWM Techniques - Ch. Lokeshwar Reddy; P. Satish Kumar; M. Sushama (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Five control algorithms are presented in this paper for STATCOM that meets the requirement of load reactive power and correspondingly voltage balancing of isolated dc capacitors for H-bridges. The control techniques used for an inverter in this paper are Sinusoidal Phase Shifted Carrier (SPSC) PWM, Sinusoidal Phase Disposition (SPD) PWM Third Harmonic Injected Phase Shifted Carrier (THIPSC) PWM, Space Vector Phase Shifted Carrier (SVPSC) PWM, and Space Vector Phase Disposition (SVPD) PWM techniques.  The STATCOM performance for the different load changes is simulated in MATLAB environment. The performance parameters such as balancing the DC link voltage, THD for the STATCOM output currents, voltages, and reactive components supplied by the STATCOM to the load are compared for all the control strategies.